Non-destructive readout of 2D and 3D dose distributions using a disk-type radiophotoluminescent glass plate. Issue 1 (March 2015) - Kurobori, T; Maruyama, Y; Miyamoto, Y; Sasaki, T; Nanto, H
Abstract: Novel disk-type X-ray two- and three-dimensional (2D, 3D) dose distributions have been developed using atomic-scale defects as minimum luminescent units, such as radiation- induced silver (Ag)-related species in a Ag-activated phosphate glass. This luminescent detector is based on the radiophotoluminescence(RPL) phenomenon. Accurate accumulated dose distributions with a high spatial resolution on the order of microns over large areas, a wide dynamic range covering three orders of magnitude and a non-destructive readout were successfully demonstrated for the first time by using a disk-type glass plate with a 100-mm diameter and a 1-mm thickness. In addition, the combination of a confocal optical detection system with a transparent glass detector enables 3D reconstruction by piling up each dose image at different depths within the material.